(3cTa GdSJQI aj TQM GdOQIs - (3Ydj GdbRhjfjs ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf, Gdbhd aj GdJjee, hgh GdbUO dZI, bhdg JYGdi(B: ((3hdG JjeehG GdNHjK efg Jfabhf(B)(3, Cj(B: (3dG JbUOhGs
(3BNQgG (B:s
(3BNQgG(B: (3hdbhd CHj LYaQ aj NHQ SYjO Hf WQja(B: (3ef cnqaf eDekfG cGf cef Vef cShJg Edi jhe GdbjGeI, hdeG Od Ydi MUQ Gdcaf (B... (3hbO Je cJGH GdWgGQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI Edi JUGfja GdTjYI, L (B18: 27s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis